CHARACTERISTICS CHANGES OF HOVEN’S CARP FILLET (Lepobarbus hoevenii) DURING FROZEN STORAGE - Riana Silalahi; Bustari Hasan; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe aim of this research was to evaluate sensory and physicochemical quality change of fish fillet during frozen storage. Fish sample, 800-1000g in size were taken from cage culture in Ranah County, Kampar. The fish was transported to Fish Processing Technology Laboratory, filleted, washed and stored in freezer      (-20o) for 40 days. Sensory analysis, TBA, TVB, drip loss and water holding capacity were made every 10 days along storage. During storage, sensory scores, TBA, TVB, drip loss and water holding capacity changed from 9.0-7.3, 0.005-0.334 malonaldehyde/kg, 5.36-21.36 mgN/100g, 4.16-10,40%, 83.61 - 82.35%, respectively. Based on 5 as unacceptable score, fish fillets were considered acceptable up to the end of storage. Sensory scores, TBA, TVB, drip loss and water holding capacity were highly correlated to storage time with correlation value (r) -0.9406, 0.9717, 0.9924, 0.9923, -0.9830, respectively.Keyword :Leptobarbus hoevenii, physicochemical, sensory, frozen storage